2011
DOI: 10.1177/1354068811400528
|View full text |Cite
|
Sign up to set email alerts
|

From protest to power: Autonomist parties in government

Abstract: In many Western European states, an increasing number of autonomist parties are taking part in government at state and regional levels. To date, however, scholars have paid little attention to the repercussions of government incumbency for these actors. This article aims to take a first step towards redressing this oversight. Based on an extensive literature examining political parties in government, we formulate hypotheses about how autonomist parties will approach, behave within and be affected by government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 35 publications
0
52
0
3
Order By: Relevance
“…If the same party governs on several territorial levels simultaneously, internal party pressure facilitates authority shifts (Elias & Tronconi 2011: 518-520;Léon 2014;Petersohn et al 2015: 629). There is evidence from Belgium, the United Kingdom, Canada, Spain and Italy to support this argument (Elias & Tronconi 2011;Petersohn et al 2015). Electoral strength in a certain area or electoral importance for the state-wide level may empower particular subnational party branches.…”
Section: The Theory Of Ideological Authority Insulationmentioning
confidence: 99%
“…If the same party governs on several territorial levels simultaneously, internal party pressure facilitates authority shifts (Elias & Tronconi 2011: 518-520;Léon 2014;Petersohn et al 2015: 629). There is evidence from Belgium, the United Kingdom, Canada, Spain and Italy to support this argument (Elias & Tronconi 2011;Petersohn et al 2015). Electoral strength in a certain area or electoral importance for the state-wide level may empower particular subnational party branches.…”
Section: The Theory Of Ideological Authority Insulationmentioning
confidence: 99%
“…These are the political actors that tend to benefit most from the establishment of regional elections and regional governments (Brancati 2008;Massetti and Schakel 2017). This choice draws on previous works, which have suggested that: (a) the presence of regional parties create a bi-dimensional regional space (traditional left-right plus a centreperiphery dimension) that changes the dynamics of competition and government formation (Ştefuriuc 2009); (b) the number of regional parties entering regional office has increased substantively in the last two decades (Elias and Tronconi 2011); (c) strong regional parties that get into office at regional level tend to hold on to it for long periods due to their strongly identitarian appeal (Alonso et al 2015: 17); (d) they tend to be less judged (and penalised) by voters on executive performance (Alonso 2008: 101); and (e) regional parties are far from immune from the general pressure for vertical congruence in government formation (Tronconi 2014).…”
Section: Political Regionalismmentioning
confidence: 99%
“…And this is happening at a time when the internal divides within the member states are also deepening, as shown by the momentum gained by independentist parties. The presence of secessionist and independentist parties is spreading across many EU member states (Elias and Tronconi 2011;Hepburn and Elias 2011;Hepburn 2009), signalling the emergence of internal fractures that further problematise the process of integration (Laible 2008). Against such a complex backdrop, the future political direction of the EU appears increasingly uncertain, and the risk that the EU will turn into a 'club of clubs' (Majone 2014a; Majone 2014b) seems tangible.…”
Section: A Crisis Of Purposementioning
confidence: 99%